Biosensors : fundamentals and applications - Pandey, Chandra Mouli; Malhotra, Bansi Dhar (De Gruyter, 2019)
This book focuses on the state-of-the-art of biosensor research and development for specialists and non-specialists. It introduces the fundamentals of the subject with relevant characteristics of transducer elements, as well as biochemical recognition molecules. This book is ideal for researchers of nanotechnology, materials science and biophysics.